Validation of a Blended Mathematics Learning Readiness Instrument Based on Offline Delivery in Remote Areas - Heny Sri Astutik; Andi Kaharuddin; Salmawati; Murniati; Muh Jusri Kahar; Hernita Pasongli (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study aimed to develop and validate an instrument assessing student readiness for offline-supported blended mathematics learning, addressing a critical measurement gap in Indonesia's disadvantaged, frontier, and outermost (3T) regions like Southwest Papua. Design – Employing a sequential exploratory psychometric design, we addressed the internet-dependency of existing instruments. An initial 40-item pool, adapted from the Online Learning Readiness Scale for offline contexts, was refined to 30 items. Content validity was established via two expert review rounds (N=3) using NVivo 14 thematic analysis and Gregory's index. Construct validity was examined through Exploratory Factor Analysis (EFA) with 150 mathematics students, alongside Cronbach's Alpha for reliability. Findings – Content validity (Gregory's index) improved from 0.60 to 0.88. EFA established a five-factor structure for the 30 items, explaining 68.4% of the total variance: (1) Learning Independence with Local Resources (α=0.89), (2) Offline Technical Literacy (α=0.87), (3) Adaptation to Infrastructure Limitations (α=0.82), (4) Mathematics Self-Efficacy with Offline Media (α=0.91), and (5) Learning Motivation in Digital Isolation (α=0.79). Overall reliability was α=0.93. Implications – The instrument provides a valid, reliable tool for diagnosis and interventions in underserved regions. Limitations regarding geographic specificity, sample size, and unexamined criterion validity suggest directions for future cross-context validation and longitudinal studies. Originality – By introducing